PENGARUH FEE AUDIT, PENGALAMAN KERJA, DAN INDEPENDENSI AUDITOR TERHADAP KUALITASAUDIT PADA KANTOR AKUNTAN PUBLIK DI KOTA MEDAN - Fachruddin, Wan; Handayani, Sri (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2017)
This study aims to determine the effect of audit fees, work experience, and auditor independence on audit quality either partially or simultaneously. Population in this research is auditor working at Public Accounting Firm (KAP) in Medan city. This research sample was taken using a saturated sampling technique. The data used is the primary data in the form of questionnaires distributed to auditors of each KAP in the city of Medan. The questionnaires were distributed as many as 136 auditors but only 52 and 5 incomplete ones that can be used as many as 47 respondents. Data analysis techniques use multiple linear regression analysis, testing classical assumption and hypothesis testing. The result of this research is partially audit fee have an effect on audit quality, work experience berrpengaruh to audit quality, while independence of auditor does not affect to audit quality. Simultaneously audit fees, work experience, and auditor independence have an effect on audit quality.Keywords: fee audit, work experience, auditor independence, audit quality